Comparison of MACD and Stochastic in Optimizing Stock Investment Strategy - Arta, Sri Nurpiana; Haanurat, Andi Ifayani; Jaya, Asri (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p18, 2025)
The Purpose of study is to analyze the accuracy level and compare the profit levels generated using the Moving Average Convergence Divergence (MACD) and Stochastic Oscillator (SO) indicators through a comparative quantitative approach. The analysis is conducted to observe the performance differences between the two indicators in optimizing profits on IDX30 stocks. The Wilcoxon test performed to examine this comparison indicates a significant difference in the accuracy level and profit level generated between the two indicators. The results of this study show that there is a significant difference in the accuracy levels of the MACD and Stochastic indicators in optimizing profits. This is due to the fact that the MACD indicator tends to be slow in responding to price changes, especially in volatile market conditions. Additionally, the MACD indicator mostly generates false signals at a rate of 60%, while the Stochastic indicator predominantly produces true signals at a rate of 93%. The findings of this study also indicate a significant difference in the profit levels generated using the MACD and Stochastic indicators, with the Stochastic indicator being more optimal in generating profits. This is because the MACD indicator is classified as a lagging technical indicator, while the Stochastic indicator is considered a leading technical indicator. The results of this research can serve as a consideration in making decisions to buy or sell stocks. Keywords: Accuracy; Profit Optimization; MACD; Stochastic